Analisis Adiksi Tren Di Internet Terhadap Perubahan Tingkah Laku Generasi Muda - Siti Nur Afina; Cinta Mayra Zetha; Gani Hakim Abdillah; Velda Murdiana (Lembaga Pengembangan Kinerja Dosen, 2024)
The presence of the internet is inevitable and the internet has become a necessity for everyone today because with the help of the internet we can exchange messages from one another and from one place to another quickly. However, teenagers today while using the internet have not been able to categorize or filter what they consume through the internet. This article discusses trends that are widely consumed and can change the habits or behavior of its users, of course from things that lead to positive to negative impacts. Internet addiction is characterized by excessive use of the Internet due to lack of self-control and can interfere with daily activities, such as skipping class, decreased academic performance, and reduced working hours. Given the increasing number of Internet-related problems, especially games, faced by people in various parts of the world.